Sensory Profile of Cocoa Powder Using Analytical Hierarchy Process - Tunjung-Sari, Ariza Budi; Prameswari, Fitrih Salsabilah; Belgis, Maria; Amilia, Winda (Indonesian Coffee and Cocoa Research Institute, 2022)
Cocoa powder comes with various attributes in its taste affecting consumer acceptance. The analytical hierarchy process (AHP) approach can be used to identify the effect of each attribute on the sensory profile of cocoa powder. This present study used the AHP approach to determine the degree of importance of sensory attributes on several types of cocoa powder and find the type with the best sensory profile. Cocoa powder comes from cocoa beans made through fermentation and non-fermentation process. In addition, we used non-fermented cocoa powder treated with water and incubated at 45oC for 4, 8, and 16 hours later named as incubated cocoa powder. Then, the sensory attributes of fermented cocoa powder were used as the reference in assessing the sensory profile of incubated cocoa powder, including the one going through the treatment. The sensory analysis performed by trained panelists revealed 11 attributes that made up the flavor profile of cocoa powder. Of these 11 attributes, only 4 were considered primary attributes with a high degree of importance, including chocolate (23.7%), sweet (19.9%), caramel (11.8%), and nutty (10.9%). Other attributes had a lower degree of importance, including creamy (7.4%), fruity (6.5%), green (5.4%), flowery (4.8%), astringent (4.5%), bitter (3.1%), and acid (2.2%). AHP also ranked the incubated cocoa powder based on the similarity of the flavor profile with fermented cocoa powder. Nonfermented cocoa powder without treatments fell into the lowest rank, while nonfermented cocoa powder with treatments fell into a higher category in the following order: 8 hours > 16 hours > 4 hours. To summarize, AHP can be used in decisionmaking affected by many factors. AHP has been proven effective in determining the sensory profile of cocoa powder, especially in choosing the attribute withthe highest effect. In addition, AHP helps determine the best treatment for incubated cocoa powder to produce the most similar sensory profile to fermented cocoa powder.